O niektórych powiązaniach między ekspansywnością prawa karnego a państwową ingerencją w gospodarkę (perspektywa indywidualistyczna) - Lipiński, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The article deals with the issue of common elements between expansion of criminal law regulations and state intervention in the economy. Taking the perspective of individualism, the author assumes that the paternalism behind these phenomena is diﬃcult to accept. In a liberal state, the law should not be used to impose certain moral attitudes on citizens.
Keywords: indywidualizm; kolektywizm; interwencjonizm gospodarczy; paternalizm